DETERMINAN KEPATUHAN WAJIB PAJAK: KONDISI KEUANGAN SEBAGAI PEMODERASI: (Studi Empiris Wajib Pajak Badan yang terdaftar di KPP Pratama Jakarta Kebayoran Baru Dua) - Suwanti; Eva Herianti; Sulhendri (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2022)
The tax ratio from 2014 to 2020 did not show any significant development. The Covid-19 pandemic that is currently happening has caused the 2020 tax ratio to decrease to 9.73. The tax ratio can be increased by increasing tax compliance. This study aims to measure "Determinants of Tax Compliance with Financial Conditions as Moderators". The variables in this study are Tax Knowledge, Tax Sanctions, Tax Audit and Trust with Financial Conditions as Moderation Variables. The type of research used is quantitative research with a survey research form. This study uses primary data through a questionnaire, with corporate taxpayer respondents who are registered at KPP Pratama Jakarta Kebayoran Baru Dua. The sample used in this study were 169 respondents. Quantitative data analysis was performed using the Partial Least Square (SEM-PLS) technique which was processed through the SmartPls 3.0 software. This study shows that knowledge of taxation and tax sanction has a positive and insignificant effect on tax compliance, while tax audit and taxpayer trust have a positive and significant effect on tax compliance. Financial conditions are not able to moderate the influence of tax knowledge, tax sanction, tax audit and trust on tax compliance